Households' euroization in the Republic of North Macedonia: Is it close to or far from the optimal levels? - Tanja Jakimova; Milan Eliskovski; Artina Bedzeti Baftijari (National Bank of the Republic of North Macedonia, 2022)
The paper deals with the challenges stemming from the phenomenon of unofficial euroization in the Republic of North Macedonia. It tries to identify the main drivers of the households' deposit euroization in the Republic of North Macedonia and contributes to the literature by providing an empirical measure of optimal level of euroization. With focus on the household deposits, it is an additional attempt to empirically estimate the optimal level of euroization in the Republic of North Macedonia, following an already published IMF study on this issue. Looking ahead, persistence in stability-oriented macroeconomic policies and measures for promotion of the use of local currency could further support the deeuroization trend in the Republic of North Macedonia.
Keywords: C32; E47; E58; 330; euroization; local currency; financial stability; monetary policy; prudential policy; Republic of North Macedonia